(untitled) (PERcursos Linguísticos, 2023)
The discursive fable genre offers a rich opportunity for inferential reading activities that transcend the understanding of the conflict between the characters in the fabulistic narrative and allow the interpretation of the allegorical way in which the fable brings into question character traits and behavior of human beings. The discussion about moral values ​​is an aspect of human formation and critical action in the social world. Many current teaching materials, however, still have a limited approach to reading this genre. This article aims to contribute to fable reading practices, after pointing out the restricted perspectives of a fable reading proposal in current didactic material. It is based on the Bakhtinian conception of language and on the sociocognitive perspective of reading. The results show that fable can be approached through four reading procedures, articulated from the theoretical foundation. In this way, it is possible to mobilize knowledge about the genre, the theme of the fable and its relations with human behavior. It is concluded that, thus developed, the reading of the fable allows a responsive, dialogical and critical attitude towards the moral value put under discussion, in tune with the competences foreseen for the teaching of the Portuguese Language.